METHODS SUPPORTING POLICIES IN EDUCATION REFORM - Xojiyev Amonjon Ro'zi o'g'li; Mustafoev Nursultan Shavkat o'g'li (TADQIQOTLAR.UZ, 2023)
In a school room setting, superb conversation plays a fundamental position in facilitating gaining knowledge of and retaining an attractive environment. Teachers who master the art of the use of fabulous and superb language at some point of classes can significantly decorate scholar understanding, participation, and overall educational performance. This article explores key strategies and methods for using classroom language correctly to maximize the getting to know experience.